Designing a Structural Equation Model for Physical Activity Level, Job Satisfaction, and Effectiveness of Police College Officers in Iraq - Falih Hasan, Ahmed; Askari, AhmadReza; Jabbar Naser, Abduljaleel; khorvash, Majid (Health Nexus, 2025)
This study aimed to propose a structural model for the relationship between physical activity level, job satisfaction, and the effectiveness of police college officers in Iraq. The research method was applied in terms of its purpose and descriptive in terms of its nature, conducted through a survey approach. The statistical population included all police officers at the Police Academy of Iraq. Data collection was performed using standardized questionnaires, including the Physical Activity Questionnaire by Askari et al. (2013), the Minnesota Satisfaction Questionnaire (MSQ), and the Effectiveness Questionnaire by VandeWalle (2000). Data analysis employed one-sample t-tests, Sobel tests, and structural equation modeling (SEM) using LISREL software. The results indicated that job satisfaction mediates the relationship between physical activity level and the effectiveness of police college officers in Iraq. Additionally, there was a positive and significant relationship between the components of physical activity level, job satisfaction, and the effectiveness of police college officers in Iraq.